Assessment of Antarctic minke whales using statistical catch-at-age analysis (SCAA) - Punt, Andre E.; Hakamada, Takashi; Bando, Takeharu (J. Cetacean Res. Manage., 2023)
Statistical catch-at-age analysis (SCAA) is applied to data for Antarctic minke whales. The SCAA model is spatially-structured, can model multiple stocks of minke whales, and can utilise several data types for parameter estimation. The application to Antarctic minke whales considers two stocks (I and P) in five areas which cover Antarctic Areas III–E to VI–W. The parameters of the model (annual deviations about the stock-recruitment relationship, changes over time in carrying capacity, density-dependence parameters related to productivity and carrying capacity, and the parameters which determine growth by stock, age-specific natural mortality by stock, and vulnerability by area and ‘fleet’) are estimated by fitting the model to data on catches, catch-at-length, conditional age-at-length, and estimates of absolute and relative abundance. A reference case analysis is selected, and sensitivity explored using retrospective analyses and by varying the assumptions on which the reference case analysis is based. The reference case analysis is able to mimic all of the data sources adequately. Most of the analyses (reference and sensitivity) indicates that Antarctic minke whales in the assessed area increased from 1930 until the mid-1970s and have declined thereafter, with the extent of the decline greater for minke whales in Antarctic Areas III–E to V–W than for those further east. Natural mortality is consistently estimated to be higher for younger and older individuals than for individuals of intermediate age. Estimates of MSYR1+ (the exploitation rate on animals 1 and older at which sustainable yield is maximised) are presented, but are unreliable owing to the lack of contrast.